ANALISIS DAN PERANCANGAN APLIKASI SISTEM INFORMASI UJIAN BERBASIS ANDROID PADA SMKN 3 KOTA JAMBI - Saquro, Abdan; Assegaff, Setiawan (LPPM Universitas Dinamika Bangsa, 2019)
SMKN 3 Jambi city is one of the educational institutions located in the western ring I Jambi. Based on theresults of interviews that have been done, the ongoing examination process at the school is to do thedoubling of problems. This results in a variety of problems. Among them is the process of calculating thevalue of a slow because it must be calculated one by one, requires a large cost in doubling the examquestions and pay honorarium employees involved in the test process.